2012
DOI: 10.1007/s13199-012-0191-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of arbuscular mycorrhizal fungi in alleviating salt stress in Medicago sativa L. var. icon

Abstract: Medicago sativa L. is the most important forage crop in arid and semi-arid areas, where increased salinity is a major factor limiting plant growth and crop productivity. The role of arbuscular mycorrhizal (AM) fungus Glomus viscosum H.T. Nicolson strain A6 in protecting alfalfa plants from salt stress, induced by sodium chloride (NaCl), was studied in two ways. Firstly, the root systems of 3-month old M. sativa plants, both mycorrhizal (AM+) and nonmycorrhizal (non-AM) (M. sativa L. var. icon), were placed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
32
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 72 publications
11
32
0
4
Order By: Relevance
“…It was confirmed that the P5CS plays a major role in proline biosynthesis under salt stress in both salt tolerant PBG-5 and salt sensitive CSG-9505 genotypes of chickpea (Jahromi et al, 2008;Garg and Baher, 2013). Free proline and total soluble sugars are the major osmolytes in AMF-inoculated plants under salt stress that control the osmotic potential at the cellular level, leading to enhanced salt tolerant ability (Campanelli et al, 2013;Yang et al, 2014;Evelin et al, 2019). Free proline enrichment in the salt stressed plants with AMF inoculation plays a key role as osmotic adjustment (Chun et al, 2018), which confirmed the function as osmolytes by mitigation of NaCl stress in mustard plant (Sarwat et al, 2016).…”
Section: Soluble Sugar Free Proline Osmotic Potential and Their Rementioning
confidence: 82%
See 3 more Smart Citations
“…It was confirmed that the P5CS plays a major role in proline biosynthesis under salt stress in both salt tolerant PBG-5 and salt sensitive CSG-9505 genotypes of chickpea (Jahromi et al, 2008;Garg and Baher, 2013). Free proline and total soluble sugars are the major osmolytes in AMF-inoculated plants under salt stress that control the osmotic potential at the cellular level, leading to enhanced salt tolerant ability (Campanelli et al, 2013;Yang et al, 2014;Evelin et al, 2019). Free proline enrichment in the salt stressed plants with AMF inoculation plays a key role as osmotic adjustment (Chun et al, 2018), which confirmed the function as osmolytes by mitigation of NaCl stress in mustard plant (Sarwat et al, 2016).…”
Section: Soluble Sugar Free Proline Osmotic Potential and Their Rementioning
confidence: 82%
“…NaCl (mM) alfalfa cv. icon, low levels of Na + in AMF inoculated plants were demonstrated when compared with the control (Campanelli et al, 2013). In citrus (red tangerine) seedlings, Na + enrichment is generally antagonist with K + when subjected to 100 mM NaCl for 60 days and also, Na + in AMF inoculated plants (GM and Paraglomus occultum) was significantly lower than in uninoculated plants (Wu et al, 2010).…”
Section: Treatmentmentioning
confidence: 95%
See 2 more Smart Citations
“…Given the factors of environmental deterioration, unsuitable irrigation management, increasing human population, soil salinization is becoming more and more prominent . Salt stress adversely affects biological and physiological processes of plants via inducing water deficiency, osmotic stress, nutritional imbalance and ionic toxicity (Campanelli et al 2013), eventually resulting in the structural damage of plant cell, photosynthesis inhibition, growth limitation, or even death Munns and Tester 2008).…”
Section: Introductionmentioning
confidence: 99%